Mongolia - Improving Public Investment Planning and Budgeting - World Bank (World Bank, 2012)
This note focuses on the second of these reform agendas, and in particular on how the institutional and organizational system for public investment planning and budgeting can be improved. Considerable analytical work has already been done on the macroeconomic and fiscal framework, and the Fiscal Stability Law (FSL), prepared with on-going technical assistance from the International Monetary Fund and the World Bank, was recently approved by the parliament. The framework for public investment planning however is in a state of flux, and there is a risk that the rapid changes currently underway will result in fragmentation of planning from budgeting, and within planning across financing sources. The on-going changes therefore provide both an opportunity and a risk, and this note is an attempt to crystallize the Bank's on-going technical assistance in this area in one document. The note complements, and draws on, other analytical activities by the Bank, including a governance and political economy assessment of the public investment system in Mongolia, and the development of a new framework for public investment management in resource dependent countries.